Picture quality comparison between panoptic ophthalmoscope and non-mydriatic fundus camera - Mehmood, Faisal; Mehmood, Ahsan; Afzal, Awais; Irfan, Abdullah; Moin, Muhammad; Muneeb, Muhammad (Journal of Fatima Jinnah Medical University, 2020)
ABSTRACT Background: Non-mydriatic fundus photography has been shown to be a potential alternative to direct ophthalmoscopy in the emergency department. Panoptic ophthalmoscope is a newer handheld alternative to non-mydriatic fundus camera. Its advantages include greater portability and lower price. Panoptic Ophthalmoscope compatibly utilizes mobile phone’s camera to capture high definition fundus photographs, however lower in quality in comparison with a fundus camera. This study compares the picture quality between panoptic ophthalmoscope (POO) and non-mydriatic fundus camera (NMFC). Patients and Methods: This comparative cross-sectional study was conducted in Lahore General Hospital, Lahore. Three twenty three (323) fundus pictures were taken from two different cameras. One hundred sixty pictures (160) were taken with NMFC and one hundred sixty three (163) with POO. Quality of each picture was assessed by two consultant ophthalmologists independently. The data was computed and analyzed by SPSS version 21. Chi square test was applied to the data. Confidence interval of 0.95 with α of 0.05 was taken. Results: There was statistically significant difference in picture quality of disc, macula, superior and inferior vascular arcades (p<0.001). Total 122 out of 160 pictures taken by NMFC and 48 out of 163 pictures taken by POO were considered ideal by first ophthalmologist whereas 96 of 160 pictures taken by NMFC and none taken by POO were considered ideal by second ophthalmologist. Conclusion: Quality of images taken with NMFC is significantly better as compared to POO.